2017
DOI: 10.1037/hea0000499
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the placebo effect: Exploring the influence of physician characteristics on placebo response.

Abstract: This study suggests that placebo effects should be construed not as a nuisance variable with mysterious impact but instead as a psychological phenomenon that can be understood and harnessed to improve treatment outcomes. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 35 publications
7
169
3
1
Order By: Relevance
“…Experts agreed that a good patient-clinician relationship is essential to make optimal use of placebo effects to increase therapeutic efficacy (D2). Indeed, evidence is mounting that characteristics such as trust, warmth, and empathy are helpful in medical communication to foster placebo effects [38, 39]. In addition, there was clear consensus that clinicians should receive regular education and training about how to make optimal use of placebo effects in their treatments (D6 and D7).…”
Section: Resultsmentioning
confidence: 99%
“…Experts agreed that a good patient-clinician relationship is essential to make optimal use of placebo effects to increase therapeutic efficacy (D2). Indeed, evidence is mounting that characteristics such as trust, warmth, and empathy are helpful in medical communication to foster placebo effects [38, 39]. In addition, there was clear consensus that clinicians should receive regular education and training about how to make optimal use of placebo effects in their treatments (D6 and D7).…”
Section: Resultsmentioning
confidence: 99%
“…Investigators found that perceived physician warmth and competence, along with positive expectations of treatment, boosted placebo responses that ameliorated skin allergic reactions resulting from a histamine skin prick with the subsequent application of a cream with no active ingredients (Howe, Goyer, & Crum, 2017). Although these physician characteristics relate more to perceived likeability and credibility rather than empathy itself, they form part of the contextual psychosocial factors that help establish rapport with patients (see also Sussex, 2018).…”
Section: The Patient–practitioner Interaction: a Sociobiological Apprmentioning
confidence: 99%
“…Interactions that hold a business-like character and that create doubt and uncertainty around the practitioner’s skills and competence could lead to nocebo effects or to a reduction of placebo effects (Howe et al, 2017). HPA axis activation, anxiety, and the activity of the cholecystokinin system have been associated to the occurrence of nocebo effects (Benedetti, Amanzio, Casadio, Oliaro, & Maggi, 1997; Benedetti, Amanzio, Vighetti, & Asteggiano, 2006; Blasini et al, 2017).…”
Section: Connecting the Dots: A Clinical Approachmentioning
confidence: 99%
“…Howe et al 25 found that after inducing an allergic reaction in participants, those who had both positive expectations of allergy relief and who interacted with a provider who demonstrated high warmth and high competence displayed the largest reduction in their allergic reaction (as measured by the size of the weal) compared with other groups who had negative expectations and/or providers with low warmth and competence. Similarly, in an experiment involving patients with a common cold, it was found that 48 hours after the clinical encounter, those who rated their clinician as high in empathy had higher measures of interleukin 8 (an immune biomarker) and reported that their cold lasted on average 1 day less than those who rated their clinician as low on empathy 26.…”
Section: Evidence For Placebo Effects In the Clinical Encountermentioning
confidence: 99%